Guidobaldo del Monte's Mechanicorum liber - Jürgen Renn (Sources 1: Max Planck Research Library for the History and Development of Knowledge, 2010)
The book presents Guidobaldo del Monte's first book from 1577, the Mechanicorum liber, which is reprinted here in a facsimile edition. The book is a comprehensive treatise on mechanics dealing with the five simple machines, the lever, the pulley, the wheel on an axle, the wedge and the screw. Their properties were in turn derived from the workings of the balance and the lever. The idea that every mechanism can be reduced to these five simple machines goes back to Heron of Alexandria and has been transmitted to the early modern period by Pappus, while the foundational role of balance and lever goes back to the Problemata mechanica ascribed to Aristotle.